Pengaruh faktor impulsive buying behavior terhadap keputusan pembelian - Winahyu, Nejelina Ardhiani; Astono, Anjar Dwi; Iskandar, Donant Alananto (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2024)
This research investigates the influence of Perceived enjoyment and perceived usefulness on impulsive buying decisions in Shopee Live Streaming Shopping, which faces challenges in participant numbers compared to similar Platforms like TikTok. The research employs quantitative approach, and the study indicates that Perceived Enjoyment does not have a significant influence on impulsive buying decisions. Conversely, perceived usefulness exerts a positive and significant influence on impulsive buying decisions. The results demonstrate that both Perceived Enjoyment and Perceived Usefulness collectively have a positive and significant impact on impulsive buying decisions. The implications of these findings depict that, for Shopee Live Streaming Shopping consumers, purchases based on the necessity or utility of items drive impulsive buying behavior more than emotional satisfaction or entertainment alone. This study provides valuable insights to enhance marketing strategies and the development of Live Streaming shopping Platforms amidst competition with similar Platforms. Article Information:Received 3/29/2024 / Revised 4/19/2024 / Accepted 5/1/2024 / Online First 5/31/2024